2019
DOI: 10.1111/cen3.12495
|View full text |Cite
|
Sign up to set email alerts
|

Clinical burden and healthcare resource utilization associated with myasthenia gravis: Assessments from a Japanese claims database

Abstract: Objectives To compare the burden of illness for refractory and non‐refractory myasthenia gravis (MG) in Japanese patients. Methods Adults in a large Japanese health insurance claims database (1 September 2008 to 31 October 2016) were included in this retrospective, observational study if they had: at least two separate claims coded as MG by a neurologist; and continuous enrollment for 12 months after any MG claim (non‐refractory cohort) or the earliest claim associated with refractory disease (refractory cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
5
4
1
Order By: Relevance
“…The study showed that patients in England with refractory MG visit healthcare providers more frequently, are hospitalized more often and visit an ER more often than patients with non-refractory MG. These findings agree with recent analyses of US and Japanese health insurance claims data, which used similar algorithms to identify refractory patients 15,18 . The largest difference in resource utilization between the refractory and non-refractory MG cohorts was for inpatient hospitalization.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The study showed that patients in England with refractory MG visit healthcare providers more frequently, are hospitalized more often and visit an ER more often than patients with non-refractory MG. These findings agree with recent analyses of US and Japanese health insurance claims data, which used similar algorithms to identify refractory patients 15,18 . The largest difference in resource utilization between the refractory and non-refractory MG cohorts was for inpatient hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, patients with refractory MG spent more total time in hospitals since diagnosis than patients with non-refractory MG. These results are in line with those from the US and Japanese studies 15,18 and indicate that patients with refractory MG more frequently experience serious or life-threatening exacerbations and crises than patients with non-refractory MG.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations